Hadith #1138 - Sunan al-Nasa'i - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Haql bin Ziyad; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Rabi'ah ibn Kab al-Aslami; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“While the Messenger of Allah (ﷺ) was sitting with us around him, a man came in, turned towards the Qiblah and prayed. When he had finished his prayer, he came and greeted the Messenger of Allah (ﷺ) and the people with Salam. The Messenger of Allah (ﷺ) said to him: ‘And also to you. Go and pray, for you have not prayed.’ So he went and prayed, and the Messenger of Allah (ﷺ) started watching him, and he (the man) did not know what was wrong with it. When he had finished the prayer,
Grade:

Hadith #1618 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ma'mar bin Rashid معمر بن راشد; Rabi'ah ibn Kab al-Aslami; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said: ‘The best fasting after the month of Ramadan is the month of Allah, Al-Muharram, and the best prayer is prayer at night.'”
Grade:

Hadith #3877 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار; Rabi'ah ibn Kab al-Aslami; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘Whoever among you wakes up physically healthy, feeling safe and secure within himself, with food for the day, it is as if he acquired the whole world.’”
Grade: